Analisis Peran Stakeholder Dalam Pengelolaan Sub Das Liawan Das Mamasa Di Desa Tadisi - Selang, Wahyu; Rusmidin; Demma Semu, Yulsan; Ritabulan; Carong, Suparjo Razasli; Sarif, Muhammad (Pangale Journal of Forestry and Environment, 2025)
River Basin Areas (DAS) are part of regional development in Indonesia, which are interconnected with ecological concepts and involve reciprocal relationships among actors within an ecosystem. The increasing natural disasters experienced, such as floods, landslides, and droughts as a result of watershed damage, have become a serious concern. Therefore, there is a need for integrated watershed management that must involve stakeholders in natural resource management, which consists of various elements such as the community and the government, with principles of integration, equality, and a commitment to implementing sustainable natural resource management. The purpose of this research is to identify the roles and what the community has experienced in the Liawan sub-watershed, as well as to understand the performance perceived by the community in the management of the sub-watershed. This research is a qualitative study using stakeholder analysis. The results of this study indicate that several stakeholders involved in the management of the Liawan Watershed include the Provincial Forestry Office of West Sulawesi, the Tourism Office, the Karama Watershed Management Agency, the Central Mamasa Forest Management Unit, the Head of Tadisi Village, the Community of https://www.adenomyosisadviceassociation.org/hysterectomy Tadisi Village, Academics, and the Community of Tadisi Village. The assessment of watershed management performance perceived by the community based on interview results indicates that the community experiences economic benefits through social forestry programs, assistance with agricultural tools and seeds, as well as training in sustainable farming techniques. The good performance of Sub-Watershed management is perceived to provide economic benefits, improve environmental quality, and strengthen community participation in decision-making related to natural resource management in their area.